Health-related quality of life in IBD patients with long COVID under China’s normalized COVID-19 management - Runnan Wang; Lei Lei; Peizhao Liu; Mengxuan Li; Lin Wu; Juanhan Liu; Haiyang Jiang; Jianan Ren; Chaogang Fan; Tao Zheng (BMC Infectious Diseases, 2026)
Abstract Introduction Although the COVID pandemic has gradually subsided, many patients have experienced complicated long-term symptoms, collectively known as “long-COVID”, which is commonly associated with persistent discomfort and decrease in quality of life. Individuals with immune-mediated inflammatory diseases, such as inflammatory bowel disease (IBD), are particularly vulnerable in the context of COVID infection, while the influence from “long-COVID” remains unrevealed. This cross-sectional study aims to assess health-related quality of life (HRQoL) among IBD patients with long COVID and to identify factors associated with HRQoL impairment. Methods A cross-sectional survey was conducted from September 16 to October 10, 2023, among 235 IBD patients who had been treated at Nanjing BenQ Medical Center and Nanjing Jinling Hospital. The survey collected demographic data, COVID-19-related information, and HRQoL assessments using the Short Inflammatory Bowel Disease Questionnaire (SIBDQ). Statistical analyses, including Chi-square tests, non-parametric tests, and multivariate linear regression, were employed to identify factors associated with long COVID and HRQoL. Results Among 235 participants, 221 (94.04%) reported COVID-19 infection and 15 of 221 (6.79%) met the study definition of long COVID. Vaccination status differed by long-COVID status in an exploratory unadjusted comparison ( p = 0.033); this finding was based on only 15 cases and was not adjusted for confounding. Participants with long COVID had a lower median SIBDQ score than those without long COVID (43.00 vs. 53.00; p = 0.009). In the multivariable model, any post-COVID-19 symptoms and symptom duration were entered as nested indicators. A duration of ≥ 4 weeks was associated with an additional 8.52-point lower SIBDQ score beyond the association of any post-COVID-19 symptoms (B=-8.52; 95% CI, -13.85 to -3.18; p = 0.002). Conclusion Participants meeting the study definition of long COVID reported lower HRQoL than those without long COVID. However, because validated IBD activity measures were not collected, the observed difference cannot be separated from the possible effect of underlying IBD activity. The vaccination finding is exploratory. Larger prospective studies with standardized disease-activity assessment are required to confirm these associations.